Expanded polystyrene filters with increasing layer of suspended sediment in water softening technologies - Odud, L. M.; Kovalchuk, V. A. (КНУБА, 2017)
Liming is the most spread reagent water softening method. Existing edifices work with much lower productivity combined with designed. We offer to use liming method on expanded polystyrene filters with increasing layer of suspended sediment for water softening. Here are also compared effectiveness in laboratory and industrial conditions, presented equation what connects calcium and magnesium removal.
Keywords: water softening; liming method; suspended sediment layer; expanded polystyrene filling; calcium and magnesium ions; пом’якшення води; метод вапнування; шар завислого осаду; пінополістирольне завантаження; іони кальцію та магнію; умягчение воды; метод известкования; слой взвешенного осадка; пенополистирольная загрузка; ионы кальция и магния; 628.164